Analisis Pertanggungjawaban Pidana Penghinaan Terhadap Presiden Dan Pejabat Negara Di Media Sosial - Laksono, Dimas Wijoyo (Jurnal Sosial Humaniora Sigli, 2025)
District Court Decision Number 52/Pid.Sus/2020/PN Mjn and the Gunung Sugih District Court Decision Number 278/Pid.Sus/2020/PN Gns. News that indicates insults to the President and State Officials on Social Media. The problems discussed in this study are how the concept of regulating the legal provisions of the crime of insulting the President in Indonesia and Criminal Liability for Perpetrators of the Crime of Insulting the President on Social Media in  Decision Number 52/Pid.Sus/2020/PN Mjn and Gunung Sugih Decision Number 278/Pid.Sus/2020/PN Gns.  Normative juridical  research methods.In conclusion  The current application of the regulation of the legal provisions of the crime of insult is currently still regulated in Law Number 1 of 1946 in the Criminal Code which includes Article 207 concerning Crimes Against Rulers and article 310 concerning insult. Meanwhile, the provisions regarding insult to the President and Vice President in the new Criminal Code (KUHP), namely Law Number 1 of 2023 which includes Articles 218, 219, and 220, have been ratified and signed by President Joko Widodo on January 2, 2023. However, the new Criminal Code will come into force three years after that date, on January 2, 2026, although it still raises debate about the need for special protection for the President. based on Decision Number 278/Pid.Sus/2020/PN Gns, the perpetrator was sanctioned based on Article 207 of the Criminal Code or Article 28 paragraph (2) of the ITE Law. Meanwhile, in Decision Number 52/Pid.Sus/2020/PN Mjn, the perpetrator is subject to the Criminal Offense of Article 310 Paragraph (1) of the Criminal Code which regulates insult to a person's honor or good name.Keywords : Criminal Liability, President, Insult